The Scholar behind the Medal: Edward J. Dent (1876–1957) and the Politics of Music History. Issue 2 (2014) - Fauser, Annegret
ABSTRACT: This article engages with issues of musical historiography and politics – mainly in the 1930s and 1940s – through the example of Edward J. Dent, a towering figure of international musical and musicological life during that period. Dent's career was tightly interwoven with musical and musicological practice both in Britain and in the wider Western world. It offers a fascinating access point to European musical modernism on the one hand, and to mid-century concerns with the uses of music history on the other. In this article, I focus on these aspects of Dent's career and their intersections by exploring first Dent's involvement with the International Society for Contemporary Music, before turning to two further and closely related issues: Dent's scholarly work of that period – especially his turn to Handel – and his involvement in international cultural politics during the 1930s and 1940s.